Optimasi pembakaran menyeluruh pada reaktor pirolisis dalam menghasilkan bioarang dan asap cair - Kemas Ridhuan; Mafruddin Mafruddin; Alfi Al Rasyid (Universitas Muhammadiyah Metro, 2020)
Pyrolysis is a process of combustion in a reactor with less or no air. The results of this process in the form of bio-charcoal products, liquid smoke, tar, and sin gas. To obtain optimal bio-charcoal products and liquid smoke, it is necessary to develop a pyrolysis process by means of thorough combustion. This combustion has the advantage that the combustion fire will heat up the entire reactor wall so that it will speed up the pyrolysis process and the combustion temperature will be high so it will generate more products, especially liquid smoke. This study aims to determine combustion achievement temperatures in the combustion chamber and reactor as well as the efficiency of the results of bio-charcoal and liquid smoke obtained. This research was conducted at the Laboratory of Mechanical Engineering Universitas Muhammadiyah Metro, this study uses a pyrolysis reactor with a total combustion chamber and uses fine sand insulation. The condenser uses a 0.5-inch diameter copper pipe with 11 turns. Biomass fuels use sengon wood. The raw material of sengon wood is 10 kg. Data from this study are compared with research data on pyrolysis reactors that have not been optimized so that the differences are known. The results obtained are the combustion temperature in the combustion chamber in the previous conditions, namely 563° C, and the optimization conditions 651° C, then the combustion temperature in the reactor in conditions before 370° C and the optimization conditions 329° C. Liquid smoke results obtained in conditions before 0.9 liters and 1.2-liter optimization conditions. Then the results of bio-charcoal obtained in conditions before 2.0 kg and 2.5 kg optimization conditions.Keywords: Pyrolysis, comprehensive burning, liquid smoke, bio-charcoal, optimization.